TNF superfamily molecules in atherosclerosis: mechanistic insights and therapeutic translation - Luo, Jia; Zhang, Jiaying; Xie, Yunfei; Wu, Mengya; Wang, Zitong; Ma, Di (Frontiers in Immunology, 2025)
Atherosclerosis (AS) is the core pathological mechanism underlying myocardial infarction and stroke, which are among the leading causes of death worldwide. The landmark CANTOS trial provided robust validation of anti-inflammatory immunotherapy as a viable approach for AS treatment, thereby underscoring the critical role of inflammatory-immune dysregulation in the pathogenesis of AS. Members of the tumor necrosis factor superfamily (TNFSF), acting as key co-stimulatory immune checkpoints, exhibit spatiotemporally precise regulatory effects on the progression of AS. They achieve this by modulating lipid metabolic disorders, dynamic plaque evolution, and thrombotic complications. Numerous TNFSF-targeted immunotherapeutic have been introduced into clinical practice, showing significant efficacy in oncology and autoimmune diseases. This offers novel insights into the dissection of the TNFSF immune network and the development of therapeutic targets. This review aims to systematically analyze the mechanistic roles of TNFSF co-stimulatory molecules in AS pathology. It also synthesizes current clinical trial outcomes and approved drug profiles, emphasizing their great potential as biomarkers and therapeutic targets for AS and related cardiovascular diseases. Furthermore, it outlines future directions in drug discovery, highlighting that targeting TNFSF downstream signaling pathways and cell type-specific therapies may emerge as groundbreaking strategies for effective AS management.